Pengaruh Financial Attitude, Locus Of Control Internal, dan Financial Knowledge Terhadap Financial Management Behavior UMKM di Kabupaten Buleleng. - Pratiwi Saadi, Kadek; Aristia Prayudi, Made; Ayu Wulan Trisna Dewi, Nyoman (Universitas Pendidikan Ganesha, 2025)
MSMEs are a strategic sector in driving economic growth, but they still face challenges in financial management that increase the risk of non-performing loans (NPLs). This study aims to examine the influence of financial attitude, internal locus of control, and financial knowledge on financial management behavior among MSME actors in Buleleng Regency. This study employs a quantitative approach using a survey method targeting 264 SME operators in Buleleng District, selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed via multiple linear regression. The results indicate that financial attitude, internal locus of control, and financial knowledge have a positive and significant influence on financial management behavior. These findings indicate that the financial management behavior of SME actors is not only determined by technical capabilities but also by psychological factors and financial knowledge. The better an individual's attitude and perception toward finance, and the higher their knowledge, the better their behavior in managing business finances.